2008
DOI: 10.1093/ndt/gfn572
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the glomerular density and size in serial renal biopsies during the progression of IgA nephropathy

Abstract: Background. Although there have been many reports on clinicopathological studies of IgAN, information is limited regarding the long-term evolution of a renal histology by analysing samples obtained not only during normal renal function but also after the establishment of an impaired renal function in individual patients. Methods. We analysed 18 pairs of serial biopsy specimens from 18 patients with IgA nephropathy (IgAN) in whom the first renal biopsies were performed while normal renal function was still pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
(42 reference statements)
1
18
0
1
Order By: Relevance
“…9,10 Além disso, estudos prévios já demonstravam que a atrofia tubular/ fibrose intersticial são preditores de pior prognóstico, refletindo em longo prazo em um rim com déficit de funcionamento por lesões crônicas. 22,[31][32][33] Nossa casuística também evidenciou maiores cifras de proteinúria de 24 h em pacientes M1 em relação a M0. Tais achados são ratificados nos estudos de Kang et al 27 e Halling et al 29 , na própria classificação de Oxford, 9,10 entretanto não foram encontrados na casuística Alamartine et al 28 e Shi et al 30 A hipercelularidade mesangial, segundo alguns estudos prévios, poderia se relacionar a pior prognóstico de função renal por evidenciar presença de lesão renal ativa, o que, quando identificado, necessitaria de um tratamento mais potente aos pacientes.…”
Section: Discussionunclassified
“…9,10 Além disso, estudos prévios já demonstravam que a atrofia tubular/ fibrose intersticial são preditores de pior prognóstico, refletindo em longo prazo em um rim com déficit de funcionamento por lesões crônicas. 22,[31][32][33] Nossa casuística também evidenciou maiores cifras de proteinúria de 24 h em pacientes M1 em relação a M0. Tais achados são ratificados nos estudos de Kang et al 27 e Halling et al 29 , na própria classificação de Oxford, 9,10 entretanto não foram encontrados na casuística Alamartine et al 28 e Shi et al 30 A hipercelularidade mesangial, segundo alguns estudos prévios, poderia se relacionar a pior prognóstico de função renal por evidenciar presença de lesão renal ativa, o que, quando identificado, necessitaria de um tratamento mais potente aos pacientes.…”
Section: Discussionunclassified
“…Interestingly, we found a close inverse correlation between these two histological variables. Our previous studies have shown that there is also a close inverse correlation between GD and GV in renal biopsies of patients with IgAN [12,13]. Studies on autopsy kidneys have shown a close inverse correlation between the total nephron number and GV among people who did not have any evidence of renal disease [19].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that the individual value of glomerular density (GD; the number of nonsclerotic glomeruli per renal cortical area) in a biopsy at the time of normal renal function had a sevenfold variation in IgAN [12,13]. In addition, a low GD in the biopsy was associated with both enlarged glomeruli and a poor long-term renal prognosis in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…We recently performed a study using pairs of serial biopsy specimens from 18 patients with progressive IgAN (8). In these patients, renal biopsies were performed both before and after the establishment of impaired renal function.…”
mentioning
confidence: 99%